2003
DOI: 10.1007/s00284-003-4097-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Linkage Between Secreted Insecticidal Toxins in Natural Isolates of Bacillus thuringiensis

Abstract: Little is known about the occurrence and linkage between secreted insecticidal virulence factors in natural populations of Bacillus thuringiensis (Bt). We carried out a survey of 392 Bt strains isolated from various samples originating from 31 countries. The toxicity profile of the culture supernatants of these strains was determined individually against Anthonomus grandis (Coleoptera) and Spodoptera littoralis (Lepidoptera). We analyzed beta-exotoxin I production and searched for the genes encoding Vip1-2, Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
4
23
0
5
Order By: Relevance
“…Whereas only around 10% of the isolates showed vip1 or vip2 gene amplification, almost half of them contained genes belonging to the vip3 family (Hernandez-Rodryguez et al, 2009). This frequency of vip3 genes was similar to that observed by Espinasse et al (2003). This finding can explain the only using of VIP3 in this study for further purification and inscectisidal activity determination against whitefly.…”
Section: Purification and Insecticidal Activity Of Vips Against Whiteflysupporting
confidence: 89%
“…Whereas only around 10% of the isolates showed vip1 or vip2 gene amplification, almost half of them contained genes belonging to the vip3 family (Hernandez-Rodryguez et al, 2009). This frequency of vip3 genes was similar to that observed by Espinasse et al (2003). This finding can explain the only using of VIP3 in this study for further purification and inscectisidal activity determination against whitefly.…”
Section: Purification and Insecticidal Activity Of Vips Against Whiteflysupporting
confidence: 89%
“…These results strongly suggested that the vip3Aa16 gene is transcribed by a 35 holoenzyme, the B. thuringiensis homolog of E (39). Genes coding for Vip3 proteins are commonly found among B. thuringiensis strains, and hence, some studies have even found them in 50% and up to 87% of the strains tested and in Ͼ90% of strains carrying cry1 and cry2 genes (20,21,(40)(41)(42)(43)(44). vip3 genes are ϳ2.4 kb in length, and they are normally carried on large plasmids (43,45), although in some cases, they have been proposed to be located in the bacterial chromosome (46).…”
Section: The Vip3 Lepidopteran-active Proteinmentioning
confidence: 96%
“…On the other hand, Mesrati et al [26] revealed by southern blot the location of the vip3 gene on the megaplasmid that carries the cry1Ia gene. Likewise, Espinasse et al [35] showed that insecticidal toxins were not widespread randomly in B. thuringiensis populations, with a significant linkage observed between vip3 and cry1I and between vip1, vip2 and beta-exotoxin I production.…”
Section: Discussionmentioning
confidence: 95%